1991
DOI: 10.1042/bj2800515
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by pertussis toxin of the activation of Na+-dependent uridine transport in dimethyl-sulphoxide-induced HL-60 leukaemia cells

Abstract: The effects of pertussis toxin on the Na(+)-dependent transport of uridine were studied in HL-60 leukaemia cells induced to differentiate along the granulocytic or monocytic pathways by dimethyl sulphoxide (DMSO) or phorbol 12-myristate 13-acetate (PMA) respectively. Pertussis toxin at 50 ng/ml completely inhibited the activation of Na(+)-dependent uridine transport and consequently prevented the formation of intracellular pools of free uridine which occurs in HL-60 cells induced to differentiate by DMSO. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…First, in intact myeloid cells, inhibitory effects of PTX on "basal" activities have been repeatedly observed. Specifically, PTX reduces basal inositol phosphate production in human neutrophils and HL-60 cells (81,82), Na ϩ -dependent uridine uptake in HL-60 cells (83), and basal Na ϩ entry in rabbit neutrophils (84). It should also be mentioned that PTX can inhibit apparently agonist-independent long term events in HL-60 cells such as Me 2 SO-induced differentiation (85).…”
Section: High Constitutive Activity Of the Human Fpr: Implications Fomentioning
confidence: 99%
“…First, in intact myeloid cells, inhibitory effects of PTX on "basal" activities have been repeatedly observed. Specifically, PTX reduces basal inositol phosphate production in human neutrophils and HL-60 cells (81,82), Na ϩ -dependent uridine uptake in HL-60 cells (83), and basal Na ϩ entry in rabbit neutrophils (84). It should also be mentioned that PTX can inhibit apparently agonist-independent long term events in HL-60 cells such as Me 2 SO-induced differentiation (85).…”
Section: High Constitutive Activity Of the Human Fpr: Implications Fomentioning
confidence: 99%
“…Differentiation has also been observed in vivo in acute myelocytic leukemia patients receiving tiazofurin (51). There has been some suggestion for the involvement of a G-protein modulated signal transduction pathway in the neutrophilic differentiation of HL-60 cells (33). NB4 cells can be terminally differentiated to granulocytes with retinoic acid (29,47) and to monocytes with the combination of 12-O-tetradecanolyphorbol-13-acetate and 1,25-dihydroxyvitamin D 3 (52).…”
Section: Table I Initial Transport Rates For Nucleoside Transport In mentioning
confidence: 99%
“…Nucleoside transport processes appear to be regulated during cellular differentiation (21,33). HL-60 cells induced to differentiate to neutrophils by treatment with dimethyl sulfoxide (53), retinoic acid, or tiazofurin (an IMP dehydrogenase inhibitor) show a decrease in intracellular GTP and GDP pools (49,50,53) and an increase in the salvage of guanosine and guanine (50).…”
Section: Table I Initial Transport Rates For Nucleoside Transport In mentioning
confidence: 99%
See 1 more Smart Citation
“…4, 7-9) Lee and co-workers indicated that both equilibrative and Na + -dependent nucleoside transport systems are expressed in undifferentiated HL60 cells, but only low levels of Na + -dependent uridine transport exist in the cells. [10][11][12] On the other hand, human monocytes/macrophages have been reported to possess equilibrative nucleoside transporters. 4,5) However, the expression of Na +dependent nucleoside transport systems in such cells is controversial.…”
Section: Introductionmentioning
confidence: 99%